Delay in healthcare seeking and associated factors among patients presenting with sexually transmitted infection symptoms in the Horo Guduru Wollega Zone, Oromia, Western Ethiopia, 2022 - Guddu, Getachew Abebe; Getahun, Ayantu; Yadesa, Girma; Tolossa, Tadesse (Frontiers in Reproductive Health, 2024)
Background: Sexually transmitted infections (STIs) are the most prevalent communicable diseases that impact people's health and well-being. One of the main obstacles to successful STI prevention and control is the delay in seeking healthcare, which can result in significant personal and economic losses. However, there were limited studies on the delay in healthcare seeking among STI patients in resource limited countries such as Ethiopia.Objective: To assess delay in health care seeking and associated factors among patients presenting with STIs to public health facilities in Horo Guduru Wallaga Zone, Oromia,Methods: A cross-sectional study was conducted at public health facilities in Horo Guduru Wallaga Zone from March 15 to May 15, 2022. The study included 507 participants and used a consecutive sampling method. The outcome variable of the study was delay in health care seeking of STI patients. A binary logistic regression model was used to identify candidate variables with a p-value less than 0.25 after analyzing each variable separately.Finally, a multivariable analysis was performed to determine statistically significant variables at a p-value less than 0.05 and an adjusted odds ratio was reported.The proportion of individuals with STIs who delayed seeking healthcare in Horo Guduru Wallaga Zone was 61.3% (95%CI: 57%, 65.5%). Factors such as age >35 years (AOR = 2.23, 95% CI: 1.26, 3.95), higher educational level (AOR = 2.72, 95% CI: 1.55, 4.74), lack of condom (AOR = 1.63, 95% CI: 1.05, 2.55), and travel time to health facilities > 1 hour (AOR = 4.30, 95% CI: 1.70, 10.89) were found to be significantly associated with delayed health care seeking.This study found that the magnitude of delay in seeking healthcare was higher than the national average, and identified several factors that may contribute to the delay. Interventions such as developing educational programs and improving access to healthcare services are crucial for supporting patients with STIs.Enhancing healthcare accessibility in rural areas and promoting condom use through targeted community outreach can reduce travel time and prevent delays in seeking healthcare for STIs.